Eigenvalues of multipart matrices and their applications - Ranjit Mehatari (The American Journal of Combinatorics)
A square matrix is called a multipart matrix if all its diagonal entries are zero and all other entries in each column are constant. In this paper, we describe various interesting spectral properties of multipart matrices. We provide suitable bounds for the spectral radius of a multipart matrix. Later on, we show applications of multipart matrices in spectral graph theory.